Investigate the Importance of the Promotion factor in the Marketing of Therapeutic Tourism Services - Fatemeh Najafipour Moghadam; Irvan Masoudi Asl; Somayeh Hessam; Mahmoud Mahmoudi Majdabadi Farahani (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Medical tourism represents the travel of individuals to receive health care and treatment to another country. One of the important factors in the marketing of medical tourism is promotion. The purpose of this study is to investigate the importance of promoting factor in the proposed marketing pattern of medical tourism services. Methods: This study is a Descriptive-Correlational research method and an applied research in terms of purpose conducted in2017. The statistical population of the study consisted of all staff of medical centers and active units in the medical tourism area of the medical Science Universities in Iran and 630 of them were selected as a statistical sample by using simple sampling method. The data collection tool was a questionnaire with 63 questions related to tourism marketing components with scoring based on Likert scale. The validity of the questionnaire was evaluated by experts' judgment and reliability was measured by using Cronbach's alpha coefficient (0.82) and Test re Test (0.92) in SPSS22. Results: According to the standard estimates of path coefficients, the promotion factor with score of 0.98 consisted of 8 components ranked first among others was determined.  Conclusion: Considering the importance of the promotion component, Policy makers in the field of medical tourism services should pay special attention to promotion and related issues in order to properly identify the Capacities and capabilities of active centers globally.